PKM Pengembangan Usaha Ojek Online PAPAJEK dengan Pemanfaatan Teknologi Aplikasi Berbasis Android - Nurhidayah Nurhidayah; Amran Yahya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Papajek is one of the businesses that operates in online motorcycle taxi and courier services in Polewali Mandar, West Sulawesi Regency since 2018. However, until now the effectiveness of Papajek's management is still lacking, including the location of couriers and consumers being difficult to track, making it difficult for the delivery process. In addition, the pricing given to customers is still adjusted to the region, has not been determined according to the actual distance so that sometimes locations that are far enough away give the same price. To overcome this, we need an application that can be used to minimize things that are still obstacles in the operation of Papajek's online motorcycle taxis. Procurement of the Papajek application provides convenience for both drivers and consumers in using the application so that with the Papajek application it can increase the income of business actors both Papajek and Papajek's partners and can increase public knowledge about the use of technology in everyday life.